El comercio infame: capitalismo milenarista, valores humanos y justicia global en el tráfico de órganos - Scheper-hughes, Nancy (Revista de Antropología Social, 2006)
This article documents the growth of “transplant tourism” and the global traffic in human bodies, desires, and needs. Organ transplantation today takes place in a transnational space with surgeons, patients, donors, sellers and brokers following new paths of capital and technology. In general, organs flow from South to North, from third to first world, and from poorer to richer bodies, and from black and brown to whites and from females to males. The “scarcity” of organs and tissues combined with the scarcity of patients of sufficient means to pay for these expensive operations, has spawned a lucrative business driven by the market calculus of supply and demand. The spread of new medical technologies and the new needs, scarcities, and commodities –for instance, fresh organs and tissues– that they inspire raises urgent public issues concerning: the reordering of relations between bodies and the state in late modernity; the appearance of “fluid” and divisible bodies that disrupt early modern notions of the indivisible and autonomous body-self; the emergence of new forms of barter and social exchange that breach the conventional dichotomy between gifts and commodities and between kin and strangers; the interplay of magic and science; and the power of rumours and urban legends to challenge the official medical and transplant “narratives” on the meanings of life, death, and sacrifice.
Keywords: Capitalism; Body; Organs transplant; North-south; Critical medical anthropology